Analysis of the Effect of Translation Techniques on the Quality of Assertive Speech Translation using Impoliteness Theory in “The Silkworm” and “The Cuckoo's Calling” Novels - Waluyo, Yoyok Sabar; Iswara, Ratna Widya (SALEE: Study of Applied Linguistics and English Education, 2024)
The study of translation has been widely discussed and used as a research topic in the last decade, and this research contributes to that body of work. The focus of this study is on two detective novels, "The Silkworm" and "The Cuckoo's Calling.". The research focuses on utterances in the form of stating, mentioning, which are referred to as assertive utterances to express impoliteness. Building on Searle’s expansion of Austin's speech act theory, which categorizes speech acts into assertive, directive, commissive, expressive, and declarative, this study analyzes assertive speech acts in both English and their translations, using Jonathan Culpeper's Impoliteness Theory. Data were collected by purposive sampling method and analyzed by content analysis. A focus group discussion (FGD) involving translation experts, raters, and supervisors with extensive experience in translation was conducted to identify translation techniques based on Molina & Albir's framework and to evaluate the translation quality of assertive speech acts representing impoliteness, using the assessment model proposed by Nababan et al. Descriptive-qualitative method was used to explain the research data and describe the analysis. The data found that the translation technique could have a significant effect on the quality of the translation.